Mark Lundy - Value chains, impact investing and climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Keynote III: 'Value chains, impact investing and climate change' by Mark Lundy, from the International Center for Tropical Agriculture (CIAT) Filmed at the annual Science meeting of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) from 7-11th April, San Lorenzo del Escorial, Spain. For more information visit the CCAFS website: http://www.ccafs.cgiar.org